Cross-Cultural Communication in Organizations and Its Perspective on Islamic Communication - Afifah Afifah; Khadijah Hambali (IJCRE - International Journal of Culture, Religion, and Education, 2025)
This research aims to explore how linguistic and cultural differences shape communication dynamics in organizational settings, as well as to identify strategies that can effectively minimize misunderstandings. This research employs a library study design using secondary data sourced from books and online journals. The results show that company activities involve individuals from various countries, making cross-cultural communication unavoidable, with language differences being one of its main barriers. Since language is part of culture, variations in understanding or interpreting words or symbols can disrupt business or organizational processes. From an Islamic perspective, cross-cultural communication should be grounded in the values of honesty, trustworthiness, wisdom, and tolerance, as cultural differences are viewed as sunnatullah that must be approached with mutual respect. The application of Islamic communication ethics such as conveying information accurately, avoiding prejudice, and maintaining proper manners can create a harmonious and inclusive work environment. Thus, cross-cultural communication based on Islamic values not only strengthens professional relationships but also fosters brotherhood and brings blessings to the organization.